THE PARTIAL MOLAR VOLUME OF FE2O3 IN ALKALI SILICATE MELTS: EVIDENCE FOR AN AVERAGE FE3+ COORDINATION NUMBER NEAR FIVE - Liu Q.; Lange R.A. (My University, 2006)
High-temperature (867-1534 °C) density measurements were performed in air on 10 liquids in the Na2O-Fe2 O3-FeO-SiO2 (NFS) system and 5 liquids in the K2O-Fe2O3-FeO-SiO2 (KFS) system using Pt double-bob Archimedean method. Replicate measurements indicate an average reproducibility of 0.22%. Compositions (in mol%) range from 4 to 18 Fe2O3, 0 to 3 FeO, 18 to 39 Na2O, 25 to 37 K2O, and 43 to 67 SiO2. Errors in the gram formula weight are ~0.4%. The molar volumes were fitted to a linear compositional model, which gives a compositionally independent partial molar volume (±2σ) for the Fe2O3 component (V̄Fe2O3) of 41.52 ± 0.34 cm3/mol and zero thermal expansivity. The average residual to the fit is ±0.36% for our 57 measurements on 15 liquids at various temperatures. The value for V̄Fe2O3 in silicate liquids when Fe3+ is in fourfold vs. sixfold coordination is estimated to be ~45.5 ± 1 vs. ~34 ± 1 cm3/mol, respectively. Thus, the fitted value of 41.5 cm3/mol appears to reflect an average Fe3+ coordination number between 4.5 and 5.0, which is consistent with recently published X-ray absorption fine structure (XAFS) spectroscopy and molecular dynamics (MD) simulations on Fe3+-bearing silicate glasses. In the literature, vFe3+ is inferred to be present in trigonal bipyramidal sites, in contrast to the square pyramidal sites for vTi4+. The lack of a strong compositional or temperature dependence for V̄Fe2O3 in these alkaline silicate liquids, in contrast to what is observed in the literature for V̄TiO2 in similar melts, may reflect the different geometries for vFe3+ and vTi4+.